2017
DOI: 10.1002/cncr.30687
|View full text |Cite
|
Sign up to set email alerts
|

Is prostate cancer different in black men? Answers from 3 natural history models

Abstract: Background Black men in the US have substantially higher prostate cancer incidence rates than the general population. The extent to which the incidence disparity is due to prostate cancer being more prevalent, more aggressive, and/or more frequently diagnosed in black men is unknown. Methods We estimated three independently developed models of prostate cancer natural history in black men and in the general population using an updated reconstruction of PSA screening, based on the National Health Interview Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 32 publications
4
96
1
3
Order By: Relevance
“…The probabilities of referral to treatment during AS are based on a single cohort, and our model of AS assumes 100% referral of low‐risk men to AS, whereas in the United States, this is likely far from 100% . These results may not be applicable to the African American population because of the higher incidence of the disease or to men with significant comorbidities, who will likely not benefit from PSA screening …”
Section: Discussionmentioning
confidence: 99%
“…The probabilities of referral to treatment during AS are based on a single cohort, and our model of AS assumes 100% referral of low‐risk men to AS, whereas in the United States, this is likely far from 100% . These results may not be applicable to the African American population because of the higher incidence of the disease or to men with significant comorbidities, who will likely not benefit from PSA screening …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, black men have the highest mortality rate for prostate cancer of any racial or ethnic group in the United States at 2.3 times higher than the rate in white men (Table ). Studies have documented that aggressive prostate cancers are relatively more common in black men . A recent predictive modeling study of the natural history of prostate cancer concluded that black men develop prostate cancer at younger ages compared with the general male population in the United States, and they are 44% to 75% more likely to develop metastases before clinical diagnosis …”
Section: Selected Findingsmentioning
confidence: 99%
“…African American (AA) men and other men of African ancestry have the highest incidence and mortality rates of prostate cancer (PCa) in the world, resulting in the highest reported cancer health disparity . We use the term “African American” recognizing that while race is a social construct, racial classification remains extremely useful for describing general patterns of national health and health disparities, as most US health data are reported by self‐identified race .…”
Section: Introductionmentioning
confidence: 99%